The Characteristic of YouTube Video as a Media of Anemia Education in Indonesia : Video YouTube sebagai Media Edukasi Anemia di Indonesia: A Narrative Review - Helmyati, Siti; Aryanti, Lintang; Basrowi, Ray Wagiu; Pratiwi, Dessy (Amerta Nutrition, 2023)
Background: The effectiveness of Anemia program in Indonesia must be supported by good public knowledge. YouTube can be used as a learning source to educate people about anemia. Anemia educational videos on YouTube have different characteristics that are interesting to analyze. Objectives: To identify the availability and describe the characteristics of anemia educational videos on YouTube. Methods:  Videos were searched via google.com and youtube.com with the keywords "anemia education in Indonesia". Videos were screened according to the criteria. Video form, type of uploader, duration, and number of views were identified. The educational contents were analyzed based on 5 points of anemia information. Discussion: Among 115 videos obtained, 28 videos met the criteria. Most anemia videos on YouTube were animated videos (51.72%), found on non-government/private channels (41.38%), and had more than 3 minutes duration (55.17%). The average video length was 190.68 seconds, ranging from 1,033 to 77,628 number of views, and each video was viewed 24 times a day. The highest number of views were videos featuring presenters/health care professionals, videos from non-government channels, and videos with 3-6 minutes duration. Over 60% of videos explained the definition, causes, impacts, signs/symptoms, and the prevention of anemia. Conclusions: There were many different characteristics of anemia educational videos on YouTube. Besides duration and number of views, the quality of information and feasibility are important aspects in producing educational videos. Further research is needed to see the relationship between duration, video form and type of uploader on people engagement.